Evidence of Mycobacterium avium subsp. paratuberculosis (MAP) infection in huemul deer (Hippocamelus bisulcus) in patagonian fjords - Salgado, Miguel; Corti, Paulo; Verdugo, Cristóbal; Tomckowiack, Camilo; Moreira, Rubén; Durán, Karla; Avilez, Carolina; Tejeda, Carlos (Austral Journal of Veterinary Sciences, 2017)
In the Chilean coastal Patagonia, fourteen wild deer huemul faecal pellet samples were collected and cultured for Mycobacterium avium subsp. paratuberculosis detection. Six samples were positive, but only one was able to show a molecular type similar to the most common strain reported for cattle in Chile.